Challenges in Work and Employment during the COVID-19 Pandemic - Satu Kalliola; Tuula Heiskanen (Challenges, 2022)
Since 2019, we have been living and working in close connection with the threat of an infectious disease caused by the SARS-CoV-2 virus [...]